Prototype of quadrature amplitude modulation (QAM) baseband modem on a digital baseband signal processor / Ruzaimah Mahmud - Mahmud, Ruzaimah (2011)
This project presents the prototype of Digital baseband modem on Digital Signal Processing Kit. The research focuses on different modulation schemes which are 16- QAM, 32-QAM, 64-QAM, 128-QAM and 256-QAM. All these modulation are schemes simulated by using MATLAB® R2008/a Simulink. The main objective of this project is to implement the QAM baseband modem. The research continues with developing M-file MATLAB® in order to get the BER graph and at the same time to evaluate the performance of M-ary QAM system. In the implementation part, Simulink model of Mary QAM is implemented on Digital Signal Processing (DSP) Starter Kit TMS320C6713. This implementation corporate with Code Composer Studio (CCS) installed in host Personal Computer (PC). The entire simulink model is uploaded through CCS and complied into DSK.